EUROPEAN EXPERIENCES OF IMPLEMENTATION OF PUBLIC-PRIVATE PARTNERSHIP SCHEMES - Pidgaiets, Sergii (Journal of European Economy, 2017)
The progress in the market of public-private partnership in European countries was analyzed. The experiences of public-private partnership implementation in the leading countries of Europe are studied. It has been proven that in order to achieve socio-economic welfare of a country it is acceptable to apply the publicprivate partnership mechanism in the integration of interests of both public and private sectors of economy.